Analisis Pemborosan pada Alur Proses Produksi Panel Box Menggunakan Pendekatan Lean Manufacturing di PT XYZ - Moch Sholehudin; Muhammad Farrel Ardana; Muhammad Rizqi Riyadi; Sri Suci Yuniar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT XYZ is a manufacturing company that produces panel boxes using a Make-to-Order (MTO) production system. However, its production process still contains non-value-added activities that reduce operational efficiency. This study aims to identify waste in the production flow using the Lean Manufacturing approach through Value Stream Mapping (VSM). Data were collected through direct observation, process time measurement, transportation time analysis, and waiting time identification. The results indicate that the total production lead time is 75.95 minutes, value-added activities, non-value-added activities, and necessary but non-value-added activities. The dominant waste identified is waiting, which occurs at several workstations due to process queues. The findings demonstrate that VSM is an effective tool for identifying sources of waste and can serve as a basis for improving production process efficiency.